PENGARUH MOTIVASI KEDISIPLINAN DAN KEPEMIMPINAN TERHADAP PRESTASI KERJA PETUGAS KEBERSIHAN - Afrinaldy Rustam (Lembaga penelitian dan pengabdian kepada Masyarakat, 2016)
Duty by Institution at duty Market, Hygiene and Gardening is the development of hygiene area and beauty of urban region. this Area development is maximally hence from Environment Ministry will give the appreciation in the form of